Studies on haemato-biochemical profile of adult Jersey crossbred heifers during anestrus and non-hormonal induction of estrus - DAS, P K; MUTHUKUMAR, G; SANYAL, S; RAJENDRAN, D; GHOSH, P R (The Indian Journal of Animal Reproduction, 2023)
In order to assess the haemato-biochemical profiles of adult Jersey crossbred heifers during anestrus and induced estruscondition, 12 adult heifers were selected for experimental studies. The age of the heifers were in between 2.5 - 3 years. The bodyweights were ranged between 185.5 - 252 kg. Selected animals were subjected to gynaecological examination per rectum andconfirmed they were in anestrus condition. Heifers were maintained under standard managerial condition and feeding and theywere treated with anthelmintic, mineral mixture, vitamin A injections and non-hormonal herbal preparation (Sajani,Ym SarabhaiZydus) for induction of heat. Blood samples were collected during anestrus and within 12 h after onset of heat symptoms (estrus).Eight animals exhibited estrus signs among treated animals. The results revealed that the total erythrocyte count, haemoglobin,packed cell volume, serum glucose, total serum protein, serum globulin, serum aspertate transaminase, serum alanine transaminaseand serum alkaline phosphatase were significantly (P < 0.01) higher during estrus than in anestrus condition. The lymphocytecount was also significantly (P < 0.05) higher during estrus than anestrus condition. No significant differences were observed inmean corpuscular volume, mean corpuscular haemoglobin, mean corpuscular haemoglobin concentration, eosinophil count,basophil count, monocyte count, serum albumin and serum total cholesterol content between estrus and anestrus condition. Basedon the observations, ii may be concluded that good managerial practice along with treatment with non-hormonal herbalpreparation improved physiological status of the anestrus animal.
Keywords: Jersey crossbred heifer; haemato-biochemical profile; anestrus; estrus